One Big City, Three Great Libraries - Lifer, Evan St; Kanakis, Michael (Library Journal, 1996)
Discusses developments under three relatively new directors in the New York, Brooklyn, and Queens Borough Public Libraries. Highlights include budgets and fundraising, technology, mission statements, personnel, ethnicity, services, and renovations. (AEF)